Clinical and radiological outcomes of n-HA/PA66 cages in anterior spine reconstruction following total en bloc spondylectomy for tumors - Luo, Yuanrui; Xiu, Peng; Chen, Hua; Zeng, Jiancheng; Song, Yueming; Li, Tao (Frontiers in Surgery, 2023)
This retrospective study evaluated the clinical and radiological outcomes of the nano-hydroxyapatite/polyamide66 (n-HA/PA66) cage in reconstructing the anterior column of the spine after total en bloc spondylectomy (TES). A cohort of 24 patients, 20 with primary malignant tumors and 4 with metastatic malignancies, was selected. All underwent TES and anterior column reconstruction with the n-HA/PA66 cage from January 2013 to July 2023 at a single institution. Pre-operative embolization was performed on all. We documented operation duration, intraoperative blood loss, length of hospital stay, and involved level. Mechanical complications and radiological parameters such as local kyphotic angle (LKA), anterior vertebral height (AVH), posterior vertebral height (PVH), cage subsidence, and bone fusion time were evaluated. Quality of life and neurological function were gauged using tools like the Visual Analog Scale (VAS), Eastern Cooperative Oncology Group (ECOG) performance score, Karnofsky Performance Score (KPS) scale, and American Spinal Injury Association (ASIA) grading. All patients were followed for 12-127 months, averaging 39.71 months. The average operation lasted 8.57 hours with blood loss of about 1384 mL. No tumor recurrence or organ metastases were observed, though recurrence appeared in 2 living patients. Solid fusion occurred in all at a mean time of 6.76 ± 0.69 months. No cage breakage or migration was observed. Three patients showed cage subsidence, deemed clinically irrelevant. Improvements in VAS, ECOG, KPS, and ASIA scores were noted post-surgery (P < 0.05). A marked increase in AVH was observed post-surgery (P < 0.05). LKA, AVH, and PVH values at final follow-up showed no significant change (P > 0.05). The combination of TES and the n-HA/PA66 cage led to promising clinical and radiological outcomes in anterior column spine reconstruction. The material did not hinder oncological care, aiding in the long-term quality of life for spinal tumor patients.